A mesoscopic fluidic reactor for studying the bioreduction ability of biofilm in a chemical absorption-biological reduction system for NO removal. Issue 2 (3rd April 2022) - Guo, Tianjiao; Yue, Huanyu; Ma, Cunhao; Li, Sujing; Chen, Jun; Li, Wei; Zhao, Jingkai
Abstract: A chemical absorption-biological reduction process has been developed for the removal of NO x in middle and small-sized industrial boilers. Considering the gap of process and biofilms scale-up, a mesoscopic fluidic reactor was built to study the dynamic biofilm formation and Fe(III)EDTA reduction ability. The reactor was run multiple times with different biofilm formation times and was then studied by microscopy and Matlab software. Results show that the biofilm formation has great relevance to gravity and formed biofilm has a Fe(III)EDTA reduction ability of ∼5*10 −10 mol/mm 3 /h at a flow rate of 40 μL/min. This data confirms the results in the previous research and the method provides a good way to design a scaled continuous flow chemical absorption-biological reduction system.